Pineapple production in Côte d’Ivoire: history of an activity through maps - Kopeh Jean-Louis Assi (Geografares, 2025)
Presented as one of the flag crops in a good part of the Ivorian forest south in response to the crisis that punctuates the coffee-cocoa pairing, pineapple-cultivation, despite a timid start, has managed to impose itself. Its history is marked by episodes combining crisis and success despite an impact that suffers no contestation in the forest south. This study aims to make its history in Côte d’Ivoire based on cartographic supports and various secondary data. The results of the analysis of these data show that pineapple cultivation in Côte d’Ivoire, unlike that of Latin American countries, is a recent activity. The first initiatives characterized by the production of canned pineapples date back to 1949 off the coast of Ono-Salci. Thanks to the agricultural diversification policy in 1970, pineapple cultivation experienced an unremarkable spatial expansion. Geographically, the activity remains dependent on the agroclimatic conditions of the forest south, to the point of making it a specific crop of the area.